Teaching and learning mathematics : a guide to recent research and its applications - Nickson, Marilyn (London : Continuum, 2006)
This fully updated second edition synthesises the findings of the best of recent research from different parts of the world. The author covers issues as diverse as pupils' understanding and handling of number, alegbra, space and measurement and their problem solving ability and the nature of assessment and the impace of ICT.
Includes bibliography and index.
Keywords: Mathematics -- Study and teaching; Education -- Recherche